2005
DOI: 10.1523/jneurosci.1640-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

“Kiss-and-Run” Glutamate Secretion in Cultured and Freshly Isolated Rat Hippocampal Astrocytes

Abstract: Under physiological conditions, astrocytes not only passively support and nourish adjacent neurons, but also actively modulate neuronal transmission by releasing "glial transmitters," such as glutamate, ATP, and D-serine. Unlike the case for neurons, the mechanisms by which glia release transmitters are essentially unknown. Here, by using electrochemical amperometry and frequency-modulated singlevesicle imaging, we discovered that hippocampal astrocytes exhibit two modes of exocytosis of glutamate in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
179
4
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(197 citation statements)
references
References 43 publications
13
179
4
1
Order By: Relevance
“…6). Our data do not rule out the possibility that astrocytes also express vesicles that are Ϸ300 nm in diameter (21). However, the data are most consistent with the view that the SpH laden vesicles we have imaged represent Ϸ30-50 nm glutamatergic vesicles.…”
Section: Resultscontrasting
confidence: 84%
See 3 more Smart Citations
“…6). Our data do not rule out the possibility that astrocytes also express vesicles that are Ϸ300 nm in diameter (21). However, the data are most consistent with the view that the SpH laden vesicles we have imaged represent Ϸ30-50 nm glutamatergic vesicles.…”
Section: Resultscontrasting
confidence: 84%
“…The fastconfined SpH events are similar to kiss and run exocytosis, whereas the slow-spreading events likely represent full vesicle fusion. Recent amperometry experiments have provided evidence for kiss and run exocytosis from astrocytes (21). Do the distinct events described in the present study correspond to two different pools of vesicles or different modes of release of a common vesicle?…”
Section: Distinct Forms Of Pharmacologically Evoked Exocytosismentioning
confidence: 58%
See 2 more Smart Citations
“…The main neurotransmitters that are released by astrocytes are glutamate and ATP, and in what follows their release and modulation properties will be briefly described. Thanks to important experimental studies, it was shown that glutamate is released by these cells with mechanisms similar to that regulating its release from the presynaptic terminal [24][25][26][27][28][29]. The glutamate released from astrocytes can act on the presynaptic neuron by modulating its synaptic activity, or on the postsynaptic neuron by determining its depolarization.…”
Section: Astrocytes Modulate Neural Activitymentioning
confidence: 99%